2017
DOI: 10.1186/s12951-017-0276-3
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic selenium nanoparticles induce ROS-mediated necroptosis in PC-3 cancer cells through TNF activation

Abstract: BackgroundSelenium is well documented to inhibit cancer at higher doses; however, the mechanism behind this inhibition varies widely depending on the cell type and selenium species. Previously, we have demonstrated that Bacillus licheniformis JS2 derived biogenic selenium nanoparticles (SeNPs) induce non-apoptotic cell death in prostate adenocarcinoma cell line, PC-3, at a minimal concentration of 2 µg Se/ml, without causing toxicity to the primary cells. However, the mechanism behind its anticancer activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 60 publications
2
76
0
3
Order By: Relevance
“…To dig into more detail, real-time gene expression analysis of characteristic genes of different cell death pathways showed over-expression of the only necroptosis associated TNF and IRF1 genes and downregulation of AR and PSA in these cells. The over-expression of TNF and IRF1 was found to be similar to our earlier observation in PC-3 cells (19). Further, the inhibition of SeNP induced cell death under the presence of necrostatin-1, a potent necroptosis inhibitor, confirmed the cell death pathway is necroptosis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…To dig into more detail, real-time gene expression analysis of characteristic genes of different cell death pathways showed over-expression of the only necroptosis associated TNF and IRF1 genes and downregulation of AR and PSA in these cells. The over-expression of TNF and IRF1 was found to be similar to our earlier observation in PC-3 cells (19). Further, the inhibition of SeNP induced cell death under the presence of necrostatin-1, a potent necroptosis inhibitor, confirmed the cell death pathway is necroptosis.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, biogenic SeNPs synthesized by Acinetobacter, Streptomyces, and Halococcus also showed anticancer activity, however, at higher doses (13)(14)(15). Earlier in our study, we have shown that a concentration of 2 µg Se/ml of our sterically stabilized biogenic SeNPs is very effective in inducing TNF/IRF1 mediated necroptosis in PC-3 cells without compromising the viability of human peripheral blood mononuclear cell (hPBMC) (18,19). In this part of the study, the effect of biogenic SeNPs on human prostate epithelial carcinoma cells, LNCaP was investigated.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, recent evidence shows that cytotoxic effects of germanium NPs (4 nm) are blocked by necrostatin-1, suggesting that NPs may also induce necroptosis [87]. A very recent paper reports that selenium (Se) NPs induce ROS-mediated necroptosis in PC-3 cells following cellular internalization [88].…”
Section: Necrosis Triggered By Npsmentioning
confidence: 99%
“…These include, for example, disruption of the activity of the members of HOX family of transcription factors in AML (97); inhibition of Aurora kinase A in pancreatic carcinoma cells (98); PPARγ-induced Annexin A1 expression in triple negative breast cancer cells, promoting cIAP1-degradation and, thus, activation of RIPK1-dependent cell death (99); activation of MLKL by ceramide liposomes in ovarian carcinoma cells (100); induction of ROS-dependent TNFα synthesis and necroptosis by selenium nanoparticles in PC-3 human prostate cancer cells (101); and activation of mitochondrial stress and autophagy-dependent necroptosis by BH3 mimetic drug Obatoclax (GX15-070) in human oral cancer cells (102). These and other recent findings indicate that exciting new strategies to therapeutically activate RIPK1/ RIPK3-dependent pathways in human cancers may be possible in the near future, but further effort to translate these initial findings into clinically relevant approaches is required.…”
Section: As D I S C U S S E D a B O V E A C T I V A T I O N O F R Imentioning
confidence: 99%